2018
DOI: 10.1111/jai.13821
|View full text |Cite
|
Sign up to set email alerts
|

Optimal stocking density for beluga, Huso huso , and ship sturgeon, Acipenser nudiventris during the grow‐out phase

Abstract: Summary The influence of three different initial stocking densities (SD) in flowthrough systems was evaluated on growth performance and feed utilizaition in beluga, Huso huso, and ship sturgeon, Acipenser nudiventris, juveniles in three different grow‐out phases for 228 days. In each grow‐out phase, fish were randomly distributed in 18 concrete square tanks (2.0 × 1.0 × 1.2 m3; 2 m3 of volume) according to the experimental SD. At the first phase, both fish species were subjected to three SD including 1.5, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In the current study, stocking density was not observed to affect the FCR values of Siberian sturgeon, which could indicate that the digestion and assimilation of the feed was not affected by the higher stocking density. Similar results were obtained in the rearing of fringebarbel sturgeon, Acipenser nudiventris Lovetsky, and Amur sturgeon (Ni et al 2016, Feshalami et al 2019). These results differ from those obtained with other sturgeon species, such as beluga and Atlantic sturgeon, in both of which the adverse effects of increased stocking density resulted in increased FCR values and lower growth (Rafatnezhad et al 2008, Szczepkowski et al 2011.…”
Section: Discussionsupporting
confidence: 67%
“…In the current study, stocking density was not observed to affect the FCR values of Siberian sturgeon, which could indicate that the digestion and assimilation of the feed was not affected by the higher stocking density. Similar results were obtained in the rearing of fringebarbel sturgeon, Acipenser nudiventris Lovetsky, and Amur sturgeon (Ni et al 2016, Feshalami et al 2019). These results differ from those obtained with other sturgeon species, such as beluga and Atlantic sturgeon, in both of which the adverse effects of increased stocking density resulted in increased FCR values and lower growth (Rafatnezhad et al 2008, Szczepkowski et al 2011.…”
Section: Discussionsupporting
confidence: 67%
“…The stocking density in aquaculture is a critical parameter that directly affects water quality, survival rate, feed intake, growth, immune system, gene expression, and reproduction (fertility) (Feshalami et al, 2019;Hastein et al, 2015;Jia et al, 2016;Luna et al, 2018;Minaz & Kubilay, 2021;Yarahmadi et al, 2016). Therefore, stocking density plays a key role in production and profits.…”
Section: Discussionmentioning
confidence: 99%